2020
DOI: 10.5530/ijper.54.2.44
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluations of Biodegradable Polyacrylamide Grafted Moringa Bark Gum Graft Copolymer (MOG-g- PAAM) as Biomedical and Controlled Drug Delivery Device Synthesized by Microwave Accelerated free Radical Synthesis

Abstract: Aim:The present work is based on preparation of different grades of Moringa Bark Gum (MOG) with Acrylamide (AM) with varying amount of AM (monomer) and APS (redox initiator) using microwave accelerated free radical reaction. Objectives: In the current work, the Moringa bark gum grafted with acrylamide graft copolymer was tested for tissue engineered polymeric scaffold as well as controlled drug delivery system using metronidazole as a model drug. Methodology: The microwave radiation process was used along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…If degree of hemolysis is below the hemolysis index of 2%, a material is considered as non-hemolytic according to the American Society for Testing and Materials (ASTM). (Roy et al 2020 ) (Rai et al 2020 ) Therefore, the optimized sample CrNF(S7-CL) can be concluded as safe and can be explored in biomedical and tissue engineering (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…If degree of hemolysis is below the hemolysis index of 2%, a material is considered as non-hemolytic according to the American Society for Testing and Materials (ASTM). (Roy et al 2020 ) (Rai et al 2020 ) Therefore, the optimized sample CrNF(S7-CL) can be concluded as safe and can be explored in biomedical and tissue engineering (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The acrylamide and guar gum grafting was established by a sharp peak at 1670cm -1 which signified the carbonyl group of amide moiety of the grafted acrylamide chain and was not detected in guar gum spectrum. The -NH stretching of the graft polymeric network at 3186cm -1 was coincided with a broad peak lying between 3858cm -1 and 2940 cm -1 of hydroxyl group of guar gum (Rai et al, 2020).…”
Section: Ftir Characterization Of Unloaded Grafted Polymer Of Guar Gu...mentioning
confidence: 87%
“…Polysaccharides, which are requisite polymers found in plants, animals, fungi, and bacteria, are one of the leading trends in modern medicine [ 1 , 2 ]. Due to their nontoxicity, affordability, ease of availability, biosafety, biodegradability, and widespread regulatory approval, natural polysaccharides outperform synthetic ones in many ways [ 3 , 4 , 5 ]. Natural polysaccharides exhibit adequate biological properties but are less suitable as drug carriers than synthetic polymers, as their structure and property correlation revealed certain drawbacks.…”
Section: Introductionmentioning
confidence: 99%